Representasi Terorisme Dalam Pemberitaan Online Era Pandemik Covid 19 : Analisis Isi Media Online di Indonesia, tahun 2020-2021 - Ilham Prisgunanto (Prisani Cendekia Institute, 2022)
Abstract: Terrorism is a criminal act of serious crime, because it can cause mental terror and undermine the sovereignty of a country. Acts of terror will usually threaten the lives of mankind, such as; bombing, hijacking to kidnapping and murder. This heinous act is related to a purpose, namely to win the interests of the group that is wrapped in the ideological coercion in it. This study wants to see the construction of terrorism representations from online media in Indonesia during the Covid 19 pandemic. It is so interesting to see how terrorists are depicted in this pandemic era. The theory used in this study is content analysis and is more of a framing model that seeks to frame existing phenomena. The research methodology using the Gamson and Modigliani framing model from 2.030,000 data was filtered into 300 narrative data. The findings first state that terrorism during a pandemic is so terrible, especially since it is known that the Covid-19 pandemic has made the country's economy slump and has made the ideology of terrorism vulnerable to entry into society. The two conditions that are safe and peaceful from terrorism and radicalism are the success of the police officers making arrests for prevention, not law enforcement. Third, the distribution of aid funds is prioritized for victims and prisoners, which is a form of high concern for the authorities for terrorist perpetrators and victims. Fourth, there has been a terrorist fundraising in various forms of religious activities so that it is completely obscure. Finally, fifth, it is recognized that the war on terrorism and radicalism is more targeted at the digital crime world war through social media. Therefore, such hoaxes and hate speech need to be monitored in order to understand the movements and work operations of the perpetrators of terrorism and radicalism.